The correlation between Epicardial Adipose Tissue Thickness and Severity of Coronary Artery Disease; An Echocardiographic Evaluation - Bayat, Fariba; Bahramnejad, Aliya (Archives of Men’s Health, 2021)
Introduction: Epicardial adipose tissue (EAT), as a visceral adipose tissue, is associated with various cardio-metabolic risk factors, such as fasting plasma glucose, systemic blood pressure and serum low-density lipoprotein. Using EAT thickness as a cost-efficient assessment tool for stratifying the risk of coronary artery disease (CAD) is still controversial. Methods: We enrolled 250 consecutive patients who underwent coronary angiography during 2016 and gathered their demographic. Echocardiographic examinations were performed in the left lateral decubitus position and EAT thickness was measured in standard parasternal long-axis (PLAX) and apical four chamber views. Results: 250 patients including 156 men (mean age: 57.66) and 94 women (mean age: 61.19) were enrolled. Two vessel disease (2VD) and three vessel disease (3VD) were significantly associated with hyperlipidemia (P: 0.04), CKD (Chronic Kidney Disease) (P: 0.001), diabetes mellitus (P: 0.001) and smoking habits (P: 0.001). Also, EAT thickness in PLAX view (P<0.001), and not four chamber view (P: 0.136), was significantly associated and correlated with increased involvement of coronary arteries in catheterization. Conclusion: Although EAT thickness in PLAX view was significantly correlated with 2VD and 3VD, this correlation was not strong and the accuracy of this approach needs further evaluation.